Pengaruh Religiusitas dan Literasi Zakat Terhadap Tingkat Kesadaran Pembayaran Zakat Tijarah Para Produsen Tahu dan Tempe - Mohammad Wildan Alghifari Zain; Nunung Nurhayati; Udin Saripudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The obligation to pay zakat tijarah (zakat on trade assets) is an important part of Islamic economic practices, especially for Muslim business owners. However, in various regions, including Indramayu Regency, the level of awareness and compliance of business owners, such as tofu and tempeh entrepreneurs, is still relatively low. This study aims to analyze the influence of religiosity and zakat literacy partially and simultaneously on the level of awareness of zakat tijarah payments among tofu/tempeh entrepreneurs in Indramayu Regency. This study uses a quantitative approach with a survey method and distributing questionnaires to entrepreneurs as respondents. Data were analyzed using multiple linear regression. The results show that partially the influence of religiosity on awareness of zakat payments is 68.1% and the influence of zakat literacy on awareness of zakat payments among tofu/tempeh entrepreneurs in Indramayu Regency is 63.5%. Meanwhile, simultaneously, the variables of religiosity and zakat literacy have a significant effect on the level of awareness in paying zakat tijarah by 72.4%. These findings show the importance of increasing religious understanding and knowledge about zakat as a strategic effort to increase compliance with the obligation of zakat tijarah